Tata Kelola Kolaboratif dalam Pembangunan Ibu Kota Nusantara: : Analisis Skema Kerja Sama Pemerintah dan Badan Usaha - Anisa Choirin NM Ririn; Izzati Alya Susanto alya; Taza Fattricia Taza; Mawar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2026)
The development of Indonesia’s Nusantara Capital City (IKN) constitutes a strategic public policy aimed at promoting more balanced regional development and transforming national governance practices. Fiscal capacity constraints have encouraged the government to optimize the Public–Private Partnership (PPP) scheme not only as an alternative financing instrument but also as a policy collaboration mechanism. This article seeks to analyze collaborative governance in the development of IKN through the PPP scheme by positioning the IKN Authority as the central actor within the collaborative governance framework. This study adopts a qualitative approach using a literature review and policy document analysis, particularly examining Law No. 3 of 2022 on the State Capital and Presidential Regulation No. 38 of 2015 on Public–Private Partnerships. The analysis applies the collaborative governance framework, encompassing starting conditions, institutional design, facilitative leadership, and collaborative processes. The findings indicate that, at the normative level, the governance of PPPs in the development of IKN is supported by a relatively strong legal and institutional framework. However, at the implementation level, collaboration continues to face challenges, including resource asymmetries among actors, the complexity of cross-sectoral coordination, and the need to strengthen accountability and transparency mechanisms. Therefore, the effectiveness of PPPs in supporting the development of IKN largely depends on the quality of collaborative governance that is implemented consistently and sustainably.